Decoding Skills: How These Skills are the Answer to the Reading Problem That Affects Most Students - Guenin, Laura J. (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
Decoding skills are the answer to major reading issues for students. This report examines different ways that decoding words can effectively increase a student’s reading comprehension level, and analyzes particular decoding strategies for teachers to implement with their students. This will help each student to enhance their own ability to comprehend what he or she is reading. It also compares two different teaching approaches. One uses decoding strategies and the other is a whole language approach that only deals with words in context. This document also shares the research on decoding that explains how students can decode unfamiliar words. It shows that teachers who implement decoding skills with their students will have the best strategies for teaching struggling readers.